EFFECT OF CHRONIC HASHISH CONSUMPTION ON LIVER FUNCTION AND COAGULATION PROFILE IN HASHISH USERS - Ullah, Asmat; Khan, Abad; Iqbal, Zafar; Khan, Ismail; Ahmad, Lateef; Kaleem, Waqar Ahmad; Sakhi, Mirina; Jahan, Saqib; Ahmad, Munir (Journal of Postgraduate Medical Institute, 2019)
Objective: To study the effect of hashish consumption on liver function and coagulation parameters. Methodology: Chronic hashish consumers (n=62) and healthy controls (n=43) were studied. Serum bilirubin, Liver enzymes alanine transaminase and alkaline phosphatase were studied to evaluate hepatic malfunctioning using manual colorimetric method. The coagulation parameters prothrombin time and activated partial thromboplastin time were studied to evaluate the risks of bleeding disorders using manual-tilt method. Results: An increase in the blood levels of total bilirubin (P= 0.014), alanine transaminase (P= 0.024) and alkaline phosphatase (P= 0.025) was observed in chronic hashish consumers as compared to the non-hashish using group. A significant prolongation in prothrombin time (P= 0.026) and activated partial thromboplastin time (P= 0.029) was found in chronic hashish consumers as compared to the control group. Conclusion: An increase in the levels of liver enzymes and coagulation parameters were observed in hashish users as compared to the control group which indicates that hashish consumption affect the liver functions.